Craniomaxillofacial dissimilar metal bone implant with antibacterial property and preparation method thereof

The porous skeleton is prepared through additive manufacturing technology and filled with zinc powder. Combined with the deposition of nanosilver-anti-bacterial peptide complex peptide solution, the shortcomings of existing implants in antibacterial and mechanical properties are solved, and efficient bone healing and safety of craniomaxillofacial bone implants are achieved.

CN119733095AActive Publication Date: 2025-04-01JILIN UNIVERSITY

Patent Information

Application Number
CN202510253705.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-01
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

Existing medical implants have shortcomings in antibacterial and mechanical properties, which are difficult to meet the complex mechanical needs of different areas of the craniomaxillofacial bone, and traditional preparation methods cannot accurately control the pore structure.

Method used

Additive manufacturing technology is used to prepare a porous skeleton with a lattice lattice structure, and zinc powder is filled by thermal isostatic pressure method, and nano-silver-anti-bacterial peptide GL13K composite peptide solution is deposited in combination with pulse electrodeposition method to form an antibacterial coating.

Benefits of technology

The antibacterial effect of craniomaxillofacial bone implants is achieved, reducing the risk of postoperative infection, promoting bone healing, and accelerating patient recovery, while improving the mechanical properties and biocompatibility of the implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733095A_ABST
    Figure CN119733095A_ABST
Patent Text Reader

Abstract

The invention discloses a cranio-maxillofacial dissimilar metal bone implant with an antibacterial property and a preparation method thereof, and relates to the technical field of medical implant prostheses, the preparation method comprises the following steps: step 1, preparing a nano-silver-antibacterial peptide GL13K composite peptide solution with the antibacterial property; 2, based on the selective laser melting technology, titanium alloy powder is prepared into a porous framework; 3, melting zinc powder, and filling pores of the porous skeleton with the molten zinc powder to obtain a semi-finished heterogeneous metal bone implant; step 4, depositing the nano-silver-antibacterial peptide GL13K composite peptide solution prepared in the step 1 on the surface of the semi-finished heterogeneous metal bone implant prepared in the step 3 through a pulse electrodeposition method to obtain a finished heterogeneous metal bone implant; the prepared finished heterogeneous metal bone implant has a remarkable antibacterial effect, the postoperative infection risk can be reduced, and the nano-silver-antibacterial peptide GL13K composite peptide can further promote osteoblast attachment and proliferation and accelerate the bone healing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical implant prostheses, and in particular to a cranio-maxillofacial heterogeneous metal bone implant with antibacterial properties and a preparation method thereof. Background Art

[0002] The craniofacial bones are vital to the human body and play a key role in many aspects. The craniofacial bones form the basic framework of the face, giving each person unique facial features. At the same time, the craniofacial bones protect the brain, the most important organ of the human body. Due to vehicle collisions, violent attacks, sports injuries and other reasons, various injuries to the craniofacial bones are caused. Therefore, how to more efficiently repair and replace the craniofacial bones has become a hot issue in clinical medicine.

[0003] Common medical implant alloys such as titanium alloy and zinc alloy are both biocompatible medical bone implant materials, but they all have shortcomings and deficiencies at this stage. Although titanium alloy has high strength, it has poor bone-promoting properties after implantation into the human body, a long osteogenesis cycle, and a "stress shielding" effect. Although zinc alloy has good bone-promoting activity, its mechanical properties need to be improved, and its degradation rate is difficult to control. Therefore, how to combine the advantages of multiple bone implant materials and avoid their shortcomings is a new research direction for medical bone implants.

[0004] Bacterial infection is one of the most serious complications after bone implant surgery. The inflammatory response caused by bacteria can seriously interfere with the normal activity of bone cells, hinder the bone healing process, cause patients to suffer pain for a long time, and significantly prolong the recovery period. Although some craniomaxillofacial bone implants currently have certain antibacterial properties, most antibacterial craniomaxillofacial bone implants are still in the research and development stage. Therefore, the preparation of an antibacterial craniomaxillofacial bone implant is a hot issue in the field of bone implants at this stage.

[0005] In addition, different anatomical regions of the craniomaxillofacial bones present different stress distribution characteristics: the maxillary region is mainly subjected to vertical compressive stress, the zygomatic complex needs to deal with multi-directional shear force, and the mandibular body is mainly subjected to bending stress. Therefore, it is particularly important to design bone implants that meet the mechanical properties of different parts of the craniomaxillofacial bones.

[0006] Traditional bone implant structure preparation methods can produce structures with different porosities, but the control accuracy of pore size, shape, distribution and connectivity is relatively low. Additive technology preparation can adjust printing parameters and model design, accurately control various parameters of pores, achieve highly customized pore structures, and better meet the needs of bone cell growth, nutrient transport and vascular ingrowth. Summary of the invention

[0007] In view of the above-mentioned medical metal implants that do not have antibacterial properties and the problem of single metal "stress shielding", the present invention innovatively proposes to prepare a lattice structure that meets the mechanical properties of various regions of the craniomaxillofacial bone as a porous skeleton, and then fill zinc powder into the pores of the porous skeleton by hot isostatic pressing, and then deposit the prepared nanosilver-antimicrobial peptide GL13K composite peptide solution onto the surface of the semi-finished heterogeneous metal bone implant by pulse electrodeposition equipment, thereby completing the preparation. The Young's modulus of the prepared finished heterogeneous metal bone implant can be adjusted by controlling the porosity of the lattice structure, and an antibacterial nanosilver-antimicrobial peptide GL13K composite peptide coating is deposited on the surface of the prepared finished heterogeneous metal bone implant. The presence of the coating significantly reduces the risk of postoperative infection, promotes the attachment and reproduction of osteoblasts, and accelerates patient recovery.

[0008] To achieve the above solution, the present invention proposes the following technical solution: A method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties comprises the following steps: Step 1: preparing a nanosilver-antimicrobial peptide GL13K composite peptide solution with antibacterial properties; Step 2: Based on the selective laser melting technology, the titanium alloy powder is prepared into a porous skeleton; Step 3: melting the zinc powder and filling it into the pores of the porous skeleton to obtain a semi-finished heterogeneous metal bone implant; Step 4: Depositing the nanosilver-antimicrobial peptide GL13K composite peptide solution prepared in step 1 onto the surface of the semi-finished heterogeneous metal bone implant prepared in step 3 by pulse electrodeposition to obtain a finished heterogeneous metal bone implant.

[0009] Preferably, in the step 1, the specific method for preparing the nanosilver-antimicrobial peptide GL13K composite peptide solution with antibacterial properties is: First, a silver nitrate solution and a trisodium citrate solution are used for reduction reaction at a molar ratio of 1:5, and the trisodium citrate solution is added dropwise to the silver nitrate solution and stirred in a 93-94°C water bath. When the mixed solution turns yellow, the nanosilver solution is centrifuged using a centrifuge to collect the nanosilver solid; Adding nanosilver solid into a borax-sodium hydroxide buffer solution with a pH of 9.8 to obtain a nanosilver borax buffer solution; The GL13K mother solution was mixed with a borax-sodium hydroxide buffer solution having a pH of 9.8 to obtain a GL13K working solution; The GL13K working solution and the nanosilver borax buffer solution were mixed in equal volumes to obtain a nanosilver-antimicrobial peptide GL13K composite peptide solution; The nanosilver-antimicrobial peptide GL13K composite peptide solution was left to stand at 4°C or room temperature for 4 days to complete the self-assembly process of GL13K, and finally the nanosilver-antimicrobial peptide GL13K composite peptide solution was successfully prepared.

[0010] Preferably, in the step 4, the specific method of depositing the prepared nanosilver-antimicrobial peptide GL13K composite peptide solution onto the surface of the semi-finished heterogeneous metal bone implant by a pulse electrodeposition device is: The prepared semi-finished heterogeneous metal bone implant is used as the cathode, and the inert electrode graphite sheet is used as the anode. The two electrodes are kept parallel and vertically inserted into a quartz glass cup containing a nanosilver-antimicrobial peptide GL13K composite peptide solution. NaNO3 with a volume fraction of 5% is added as an electrolyte, and then the pH is adjusted to 6-7 using phosphate buffer. A constant current pulse is used to adjust the parameters and then perform electrophoretic deposition. During the deposition process, the nanosilver-antimicrobial peptide GL13K composite peptide will be deposited on the surface of the semi-finished heterogeneous metal bone implant. After the surface of the semi-finished heterogeneous metal bone implant is completely deposited, the power is turned off and the finished heterogeneous metal bone implant is taken out.

[0011] Preferably, in step 2, the porous skeleton is a lattice structure array.

[0012] Preferably, the lattice lattice structure array is a double-pillar hexagonal structure array, a sine ring structure array or a cosine ring structure array.

[0013] Preferably, the double-pillar hexagonal structure array is obtained by arranging the double-pillar hexagonal unit cell structure four times along the x, y, and z directions; The double-pillar hexagonal unit cell structure was prepared by the following method: First, construct a regular hexagon, construct two parallel lines between the upper and lower sides of the regular hexagon, and construct a horizontal line perpendicular to the parallel lines on both sides of the intersection of the left and right sides of the regular hexagon to obtain a hexagon with convex sides and supported in the middle. The hexagon with convex sides and supported in the middle is stretched by a length a to obtain a hexagonal structure with convex sides and supported in the middle. The hexagonal structure with convex sides and supported in the middle is arranged 90 degrees along the circumference of the center position to obtain a double-pillar hexagonal unit cell structure.

[0014] Preferably, the sinusoidal ring structure array is obtained by arraying the sinusoidal ring unit cell structure four times along the x, y, and z axes respectively; The sinusoidal ring unit cell structure was prepared by the following method: First, a sine function curve is drawn with a sine function y=Asinx(Bx+C)+D, the interval is [0, 5π], where A, B, C and D are all constants, and x and y are coordinates in the space coordinate system. The sine function curve is scanned into a sine function curve structure with a circular cross section; Draw a ring so that it is tangent to the sine function curve structure; Taking the center of the ring as the reference axis of the circular array, the sine function curve structure is circularly arrayed four times to obtain a sinusoidal closed ring structure containing a ring inside; Two mutually perpendicular pillars are added to the center of the sinusoidal closed ring structure containing a circular ring inside, so as to obtain a sinusoidal closed ring structure containing a circular ring inside and two mutually perpendicular pillars; Taking the center of the ring as the reference axis, a sinusoidal closed ring structure containing a ring and two mutually perpendicular pillars is circularly arrayed with an angle of 90 degrees to obtain a sinusoidal ring unit cell structure.

[0015] Preferably, the cosine ring structure array is obtained by arraying the cosine ring unit cell structure four times along the x, y, and z axes respectively; The cosine ring unit cell structure was prepared by the following method: First, a cosine function curve is drawn with the cosine function Y=EcosX(FX+G)+H, the interval is [-0.25π, 2.25π], where E, F, H, and G are all constants, and X and Y are coordinates in the space coordinate system. The cosine function curve is scanned into a sine function curve structure with a circular cross section; Draw a ring so that it is tangent to the sine function curve structure; Taking the center of the ring as the reference axis of the circular array, the cosine function curve structure is circularly arrayed four times to obtain a cosine closed ring structure containing a ring inside; Adding two mutually perpendicular pillars at the center of the cosine closed ring structure containing a circular ring inside, thereby obtaining a cosine closed ring structure containing a circular ring and two mutually perpendicular pillars inside; Taking the center of the ring as the reference axis, a cosine closed ring structure containing a ring and two mutually perpendicular pillars is circularly arrayed with an angle of 90 degrees to obtain a cosine ring unit cell structure.

[0016] Preferably, in step 2, the titanium alloy powder used is Ti-6Al-4V powder.

[0017] Preferably, the double-pillar hexagonal structure array is arranged in the maxillary region; the sine annular structure array is arranged in the zygomatic region; and the cosine annular structure array is arranged in the mandibular region.

[0018] According to another aspect of the present invention, there is also provided a heterogeneous metal bone implant prepared by the above method for preparing a cranio-maxillofacial heterogeneous metal bone implant with antibacterial properties.

[0019] Compared with the prior art, the present invention has the following advantages: The finished heterogeneous metal bone implant prepared by the present invention has a significant antibacterial effect and can reduce the risk of postoperative infection. The nanosilver-antimicrobial peptide GL13K composite peptide therein can also promote the attachment and proliferation of osteoblasts and accelerate the bone healing process. Different from the porous skeleton prepared by traditional processes such as sintering technology, casting, forging and machining, the additive manufacturing technology used in the present invention is faster, greatly reducing the time and economic cost, and can be designed specifically according to different positions of the craniomaxillofacial bones. After combination and splicing, the impact resistance of the craniomaxillofacial bones is effectively improved; The present invention innovatively applies a heterogeneous metal composite structure deposited with an antibacterial coating to the field of medical craniomaxillofacial bone implantation, prints a porous skeleton structure with adjustable porosity through an additive manufacturing method using a titanium alloy metal with good biocompatibility, and fills zinc powder into the porous skeleton through a hot isostatic pressing method. The prepared heterogeneous metal composite structure has good biocompatibility, controllable degradation rate, and excellent mechanical properties. Its Young's modulus can be controlled by controlling the porosity of the lattice structure. The Young's modulus is within the range of 10Gpa to 30Gpa, and the compressive strength can reach more than 200Mpa, which meets the implant bone requirements for craniomaxillofacial bones. The bionic designed sine ring cell structure and cosine ring cell structure are lighter and have stronger bearing capacity. Compared with the existing lattice structure, they have good shock absorption and energy absorption performance and can effectively transfer loads. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Flow chart for preparing nanosilver-antimicrobial peptide GL13K complex peptide solution; Figure 2 Flow chart for preparing semi-finished heterogeneous metal bone implants by hot isostatic pressing; Figure 3 Flow chart of using a pulse electrodeposition device to deposit a nanosilver-antimicrobial peptide GL13K complex peptide solution onto a semi-finished heterogeneous metal bone implant; Figure 4 Flow chart for preparing double-pillar hexagonal structure array; Figure 5 A flow chart for preparing a sinusoidal ring structure array; Figure 6 A flow chart for preparing a cosine ring structure array; Figure 7 Schematic diagram of three types of lattice structure arrays set at different positions of the craniomaxillofacial bones; Figure 8 This is a diagram showing the antibacterial effect of craniomaxillofacial bones.

[0021] In the figure: 1: trisodium citrate solution; 2: silver nitrate solution; 3: nanosilver borax buffer solution; 4: GL13K working solution; 5: nanosilver-antimicrobial peptide GL13K composite peptide solution; 6: selective laser melting equipment; 7: porous skeleton; 8: zinc powder; 9: hot isostatic pressing furnace; 10: ceramic mold; 11: titanium alloy powder; 12: semi-finished heterogeneous metal bone implant; 13: pulse electrodeposition equipment. DETAILED DESCRIPTION

[0022] In order to better illustrate the preparation process involved in the present invention and its advantages over the prior art, further explanation will be given based on the above-mentioned drawings.

[0023] See also Figures 1 to 8 As shown, a method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties comprises the following steps: Step 1: preparing a nanosilver-antimicrobial peptide GL13K composite peptide solution 5 having antibacterial properties; Step 2: Based on the selective laser melting technology, the titanium alloy powder 11 is prepared into a porous skeleton 7; Step 3: melt the zinc powder 8 and fill it into the pores of the porous skeleton 7 to obtain a semi-finished heterogeneous metal bone implant 12; Step 4: Deposit the nanosilver-antimicrobial peptide GL13K complex peptide solution 5 prepared in step 1 onto the surface of the semi-finished heterogeneous metal bone implant 12 prepared in step 3 by pulse electrodeposition to obtain a finished heterogeneous metal bone implant.

[0024] For further information, see Figure 1 As shown, in the step 1, the specific method for preparing the nanosilver-antimicrobial peptide GL13K composite peptide solution 5 with antibacterial properties is: First, a reduction reaction is carried out using silver nitrate solution 2 and trisodium citrate solution 1 at a molar ratio of 1:5, 10 mL of trisodium citrate solution 1 is added dropwise into 500 mL of silver nitrate solution 2, and the mixture is stirred in a 93-94 °C water bath for about 10 minutes. When the mixed solution turns yellow, it indicates the formation of a nanosilver solution. The nanosilver solution is centrifuged using a centrifuge to collect the nanosilver solid. The nanosilver solid was added to a borax-sodium hydroxide buffer solution at pH 9.8 to obtain a nanosilver borax buffer solution 3 with a concentration of 2 mg / mL; Mix 10 μL of 100 mg / mL GL13K stock solution with 990 μL of borax-sodium hydroxide buffer at pH 9.8 to obtain 1 mg / mL GL13K working solution 4; The GL13K working solution 4 and the nanosilver borax buffer solution 3 were mixed in equal volumes to obtain a 1 mg / mL nanosilver-antimicrobial peptide GL13K complex peptide solution 5; The nanosilver-antimicrobial peptide GL13K composite peptide solution 5 was left to stand at 4° C. or room temperature for 4 days to complete the self-assembly process of GL13K, and finally the nanosilver-antimicrobial peptide GL13K composite peptide solution 5 was successfully prepared.

[0025] For further information, see Figure 2 As shown, in the step 2, the specific method of preparing the porous skeleton 7 by using the selective laser melting (SLM) technology is as follows: before printing, the material molding chamber of the selective laser melting equipment 6 is purged with high-purity argon gas until the oxygen content in the molding chamber drops below 0.1% to reduce oxidation, the printed substrate is preheated to 200°C, and the dimensional accuracy of the porous skeleton 7 is ensured, and under the process parameters of a laser power of 100 W, a laser scanning speed of 1200 mm / s, and a layer thickness of 30 μm, the titanium alloy powder 11 with a median diameter of 50 μm is layered and continuously printed by using the selective laser melting technology, and the printed porous skeleton 7 is ultrasonically cleaned with acetone.

[0026] See also Figure 2 As shown, in step 3, the specific method of melting the zinc powder 8 and filling it into the pores of the porous skeleton 7 is: When the hot isostatic pressing method is used for preparation, the prepared porous skeleton 7 is first placed in a ceramic mold 10; The zinc powder 8 is evenly sprinkled into the pores of the porous skeleton 7. In order to ensure that the zinc powder 8 can be more fully filled into the internal pores of the porous skeleton 7, mechanical vibration can be used to assist; The ceramic mold 10 is placed in a hot isostatic pressing sintering furnace 9, and the inside of the hot isostatic pressing sintering furnace 9 is evacuated and argon gas is introduced; The hot isostatic pressing furnace 9 is heated to 700°C and heated at a pressure of 100 MPa for 2 hours; The zinc powder 8 gradually melts under the combined effects of high temperature and high pressure, and then fits tightly with the porous skeleton 7, achieving a firm bond between the two.

[0027] For further information, see Figure 3 As shown, in the step 4, the specific method of depositing the prepared nanosilver-antimicrobial peptide GL13K composite peptide solution 5 onto the surface of the semi-finished heterogeneous metal bone implant 12 through the pulse electrodeposition device 13 is: The prepared semi-finished heterogeneous metal bone implant 12 is used as the cathode, and the inert electrode graphite sheet is used as the anode. The two electrodes are kept parallel and 30 mm apart, and are vertically inserted into a quartz glass cup containing the nanosilver-antimicrobial peptide GL13K composite peptide solution 5. NaNO3 with a volume fraction of 5% is added as an electrolyte, and then the pH is adjusted to 6-7 using a phosphate buffer. A constant current pulse is used to adjust the parameters and then perform electrophoretic deposition. During the deposition process, the nanosilver-antimicrobial peptide GL13K composite peptide will be deposited on the surface of the semi-finished heterogeneous metal bone implant 12. After the surface of the semi-finished heterogeneous metal bone implant 12 is completely deposited, the power is turned off and the finished heterogeneous metal bone implant is taken out.

[0028] For further information, see Figures 2 to 8 As shown, in step 2, the porous skeleton is a lattice structure array.

[0029] For further information, see Figures 4 to 6 As shown, the lattice lattice structure array is a double-pillar hexagonal structure array, a sine ring structure array or a cosine ring structure array.

[0030] For further information, see Figure 4 As shown, the double-pillar hexagonal structure array is composed of double-pillar hexagonal unit cell structures arrayed 4 times along the x and y directions, with an array distance of 74 mm in the x-axis direction and 60 mm in the y-axis direction. Finally, the whole structure is arrayed 4 times along the z-axis direction, with an array distance of 74 mm in the z-axis direction, to obtain a double-pillar hexagonal structure array. The double-pillar hexagonal structure array has excellent anti-vibration and energy absorption characteristics and can withstand large stress loads in the vertical direction.

[0031] For further information, see Figure 4 As shown, the double-pillar hexagonal unit cell structure is prepared by the following method: First, a regular hexagon is constructed, and two parallel lines are constructed between the upper and lower sides of the regular hexagon. At the intersection of the left and right sides of the regular hexagon, horizontal lines perpendicular to the parallel lines are constructed to both sides to obtain a hexagon with convex sides and a support in the middle. The hexagon with convex sides and a support in the middle is stretched by a length b, and the thickness of b is 3 mm to obtain a hexagonal structure with convex sides and a support in the middle. The hexagonal structure with convex sides and a support in the middle is arranged 90 degrees along the circumference of the center position to obtain a double-pillar hexagonal unit cell structure. The height a of the double-pillar hexagonal unit cell structure designed by the present invention is 60 mm, and the porosity of the structure can be adjusted by adjusting the size of a and the length b.

[0032] For further information, see Figure 5 As shown, the sinusoidal ring structure array is obtained by arraying the sinusoidal ring unit cell structure four times along the x, y, and z axes respectively, with an array distance of 6π.

[0033] For further information, see Figure 5 As shown, the sinusoidal annular unit cell structure is designed to imitate the microscopic annular structure inside grapefruit peel. The designed structure has good shock absorption and energy absorption performance and can effectively transfer loads. First, a sine function curve is drawn with a sine function y=Asinx(Bx+C)+D, the interval is [0, 5π], where A, B, C and D are all constants, and x and y are coordinates in the space coordinate system. The sine function curve is scanned into a sine function curve structure with a circular cross section and a diameter of 2 mm; Next, draw a ring with a diameter of 4πmm and a cross-sectional diameter of 2mm, so that the ring is tangent to the sine function curve structure; Then, the center of the ring is used as the reference axis of the circular array, and the sine function curve structure is circularly arrayed four times to obtain a sinusoidal closed ring structure containing a ring inside; Two mutually perpendicular pillars are added at the center of the sinusoidal closed ring structure containing a circular ring inside, and the diameter of the pillars is 2 mm, so as to obtain a sinusoidal closed ring structure containing a circular ring inside and two mutually perpendicular pillars; Taking the center of the ring as the reference axis, a sinusoidal closed ring structure containing a ring and two mutually perpendicular pillars is arrayed in a circle. The angle of the circle array is 90 degrees, and a sinusoidal ring unit cell structure is obtained. In the sinusoidal annular unit cell structure designed by the present invention, A=1, B=1, C=0, D=0, and the interval length is 5π, wherein the porosity of the sinusoidal annular unit cell structure is adjusted by adjusting the four parameters A, B, C, D and the cross-sectional diameter.

[0034] For further information, see Figure 6 As shown, preferably, the cosine ring structure array is obtained by arraying the cosine ring unit cell structure four times along the x, y, and z axes respectively, with an array distance of 2π.

[0035] For further information, see Figure 6 As shown, the cosine annular unit cell structure is designed to imitate the external annular structure of grapefruit peel. The designed structure has a large vertical compressive stress and strong impact resistance. First, a cosine function curve is drawn with a cosine function Y=EcosX(FX+G)+H, with an interval of [-0.25π, 2.25π], where E, F, H, and G are all constants, and X and Y are coordinates in the spatial coordinate system. The cosine function curve is scanned into a sine function curve structure with a circular cross section and a diameter of 1 mm; Next, draw a ring with a diameter of πmm, the cross-sectional diameter of which is 1mm, so that the ring is tangent to the sine function curve structure; Then, the center of the ring is used as the reference axis of the circular array, and the cosine function curve structure is circularly arrayed four times to obtain a cosine closed ring structure containing a ring inside; Two mutually perpendicular pillars are added at the center of the cosine closed ring structure containing a circular ring inside, and the diameter of the pillars is 1 mm, so as to obtain a cosine closed ring structure containing a circular ring inside and two mutually perpendicular pillars; Taking the center of the ring as the reference axis, a cosine closed ring structure containing a ring and two mutually perpendicular pillars is arrayed in a circle. The angle of the circle array is 90 degrees, and a cosine ring unit cell structure is obtained. In the cosine annular unit cell structure designed by the present invention, E=1, F=1, H=3, G=0, and the interval length is 2.5π, wherein the porosity of the structure is adjusted by adjusting the four parameters of the cosine function E, F, H, G and the cross-sectional diameter.

[0036] For further information, see Figure 2 As shown, the titanium alloy powder 11 used is Ti-6Al-4V powder.

[0037] For further information, see Figure 7 As shown, an array of double-strut hexagonal structures is disposed in the maxillary region.

[0038] For further information, see Figure 7 As shown, an array of sinusoidal ring structures is disposed in the zygomatic region.

[0039] For further information, see Figure 7 As shown, the cosine ring structure array is arranged in the mandibular region.

[0040] Working principle of the present invention: The craniomaxillofacial bones can be regarded as a composite framework system formed by the precise connection of multiple bone structures. According to the anatomical location, it can be subdivided into the main parts such as the maxilla, zygomatic bone and mandible. This system undertakes important functions in the human body, such as chewing load, facial support and protection of neurovascular bundles. When the craniomaxillofacial bones are damaged by external impact, the chewing function and facial morphology of the patient will be significantly affected. Therefore, in the design of bone restorations, it is necessary to focus on optimizing the mechanical adaptability of the implant structure to prevent secondary damage after surgery. Biomechanical studies have shown that there is a typical path for stress transmission when the craniomaxillofacial bones are impacted: the chewing load first acts on the mandibular condyle and is transmitted to the body through the mandibular ramus; the maxillary stress mainly diffuses to the zygomatic bone through the zygomatico-alveolar ridge and forms stress concentration in the zygomaticomaxillary suture area; the zygomatic bone, as the mechanical hub of the midface, disperses the stress to the skull base and the contralateral bone structure through the zygomatico-temporal suture and the zygomatico-frontal suture. The maxillary area is mainly subjected to vertical compressive stress, the zygomatic complex needs to deal with multi-directional shear force, and the mandibular body is mainly subjected to bending stress. Traditional homogenized implant design is difficult to simultaneously meet such complex mechanical requirements, so we propose the idea of ​​designing and filling specialized lattice structures according to different locations of the craniomaxillofacial bones. Figure 7 As shown in the figure, a variety of lattice lattice structures suitable for different working conditions can be prepared by printing, and filled according to different stress areas of the craniomaxillofacial bones. For example, the double-pillar hexagonal structure array has the largest bearing capacity among the three lattice structures, and can be set in the maxillary area where the craniomaxillofacial bones first encounter impact loads to adapt to larger vertical compressive stress; similarly, the cosine ring structure array has good vibration reduction performance and can be filled in the mandibular area due to large bending stress; and the sine ring structure array has stable deformation, can effectively transfer loads, and can adapt to larger multi-directional shear forces, so it can be filled in the zygomatic area to connect the maxillary area and the mandibular area. The lattice lattice structures in the three areas play a role of mechanical locking due to different filling positions, which can give full play to the advantages of each structure and make up for the shortcomings of a single structure.

[0041] like Figure 8As shown, when the craniomaxillofacial bone of the human body is subjected to a major impact or trauma, cracks or even gaps will appear on the bone surface. In order not to affect normal life, craniomaxillofacial bone repair is required at this time. The finished heterogeneous metal bone implant prepared by the above method is used to replace or fill the gap and damage, and suture is performed after filling. After implantation into the human body, the antibacterial nanosilver-antimicrobial peptide GL13K composite peptide coating on the surface of the finished heterogeneous metal bone implant can release Ag+ and GL13k peptides, enter the bacteria, and destroy the bacterial structure, thereby achieving an antibacterial effect. At the same time, the presence of the nanosilver-antimicrobial peptide GL13K composite peptide coating can prevent the implant from being degraded prematurely due to body fluid corrosion, thereby affecting the bone repair process. On the other hand, the antimicrobial peptide components inside the nanosilver-antimicrobial peptide GL13K composite peptide can promote cell growth and reproduction, so that the cells attach and grow on the surface of the nanosilver-antimicrobial peptide GL13K composite peptide coating, and induce bone tissue to grow along the interface of the finished heterogeneous metal bone implant.

Claims

1. A method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties, characterized in that: The steps include: Step 1: preparing a nanosilver-antimicrobial peptide GL13K complex peptide solution with antibacterial properties (5); Step 2: Based on the selective laser melting technology, the titanium alloy powder (11) is prepared into a porous skeleton (7); Step 3: melting the zinc powder (8) and filling it into the pores of the porous skeleton (7) to obtain a semi-finished heterogeneous metal bone implant (12); Step 4: The nanosilver-antimicrobial peptide GL13K complex peptide solution (5) prepared in step 1 is deposited onto the surface of the semi-finished heterogeneous metal bone implant (12) prepared in step 3 by pulse electrodeposition to obtain a finished heterogeneous metal bone implant.

2. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 1, characterized in that: In the step 1, the specific method for preparing the nanosilver-antimicrobial peptide GL13K composite peptide solution (5) having antibacterial properties is: First, a silver nitrate solution (2) and a trisodium citrate solution (1) are used for reduction reaction at a molar ratio of 1:5, and the trisodium citrate solution (1) is added dropwise into the silver nitrate solution (2), and stirred in a 93-94° C. water bath. When the mixed solution turns yellow, the nanosilver solution is centrifuged using a centrifuge to collect the nanosilver solid; Adding nanosilver solid to a borax-sodium hydroxide buffer solution at pH 9.8 to obtain a nanosilver borax buffer solution (3); Mix the GL13K mother solution with a borax-sodium hydroxide buffer solution at pH 9.8 to obtain a GL13K working solution (4); Mixing the GL13K working solution (4) and the nanosilver borax buffer solution (3) in equal volumes to obtain a nanosilver-antimicrobial peptide GL13K composite peptide solution (5); The nanosilver-antimicrobial peptide GL13K composite peptide solution (5) was left to stand at 4°C or room temperature for 4 days to complete the self-assembly process of GL13K, and finally the nanosilver-antimicrobial peptide GL13K composite peptide solution (5) was successfully prepared.

3. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 2, characterized in that: In the step 4, the specific method of depositing the prepared nanosilver-antimicrobial peptide GL13K composite peptide solution (5) onto the surface of the semi-finished heterogeneous metal bone implant (12) through a pulse electrodeposition device (13) is as follows: The prepared semi-finished heterogeneous metal bone implant (12) is used as a cathode, and the inert electrode graphite sheet is used as an anode. The two electrodes are kept parallel and vertically inserted into a quartz glass cup containing a nanosilver-antimicrobial peptide GL13K complex peptide solution (5). NaNO3 with a volume fraction of 5% is added as an electrolyte, and then a phosphate buffer is used to adjust the pH to 6-7. A constant current pulse is used to adjust the parameters and then perform electrophoretic deposition. During the deposition process, the nanosilver-antimicrobial peptide GL13K complex peptide will be deposited on the surface of the semi-finished heterogeneous metal bone implant (12). After the surface of the semi-finished heterogeneous metal bone implant (12) is completely deposited, the power is turned off and the finished heterogeneous metal bone implant is taken out.

4. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 1, characterized in that: In the step 2, the porous skeleton (7) is a lattice structure array.

5. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 4, characterized in that: The lattice lattice structure array is a double-pillar hexagonal structure array, a sine ring structure array or a cosine ring structure array.

6. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 5, characterized in that: The double-pillar hexagonal structure array is obtained by arranging the double-pillar hexagonal unit cell structure four times along the x, y, and z directions; The double-pillar hexagonal unit cell structure was prepared by the following method: First, construct a regular hexagon, construct two parallel lines between the upper and lower sides of the regular hexagon, and construct a horizontal line perpendicular to the parallel lines on both sides of the intersection of the left and right sides of the regular hexagon to obtain a hexagon with convex sides and supported in the middle. The hexagon with convex sides and supported in the middle is stretched by a length b to obtain a hexagonal structure with convex sides and supported in the middle. The hexagonal structure with convex sides and supported in the middle is arranged 90 degrees along the circumference of the center position to obtain a double-pillar hexagonal unit cell structure.

7. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 5, characterized in that: The sinusoidal ring structure array is obtained by arraying the sinusoidal ring unit cell structure four times along the x, y, and z axes respectively; The sinusoidal ring unit cell structure was prepared by the following method: First, a sine function curve is drawn with the sine function y=Asinx(Bx+C)+D, the interval is [0,5π], where A, B, C and D are all constants, and x and y are coordinates in the space coordinate system. The sine function curve is scanned into a sine function curve structure with a circular cross section; Draw a ring so that it is tangent to the sine function curve structure; Taking the center of the ring as the reference axis of the circular array, the sine function curve structure is circularly arrayed four times to obtain a sinusoidal closed ring structure containing a ring inside; Two mutually perpendicular pillars are added to the center of the sinusoidal closed ring structure containing a circular ring inside, so as to obtain a sinusoidal closed ring structure containing a circular ring inside and two mutually perpendicular pillars; Taking the center of the ring as the reference axis, a sinusoidal closed ring structure containing a ring and two mutually perpendicular pillars is circularly arrayed with an angle of 90 degrees to obtain a sinusoidal ring unit cell structure.

8. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 5, characterized in that: The cosine ring structure array is obtained by arraying the cosine ring unit cell structure four times along the x, y, and z axes respectively; The cosine ring unit cell structure was prepared by the following method: First, a cosine function curve is drawn with the cosine function Y=EcosX(FX+G)+H, the interval is [-0.25π, 2.25π], where E, F, H, and G are all constants, and X and Y are coordinates in the space coordinate system. The cosine function curve is scanned into a sine function curve structure with a circular cross section; Draw a ring so that it is tangent to the sine function curve structure; Taking the center of the ring as the reference axis of the circular array, the cosine function curve structure is circularly arrayed four times to obtain a cosine closed ring structure containing a ring inside; Adding two mutually perpendicular pillars at the center of the cosine closed ring structure containing a circular ring inside, thereby obtaining a cosine closed ring structure containing a circular ring and two mutually perpendicular pillars inside; Taking the center of the ring as the reference axis, a cosine closed ring structure containing a ring and two mutually perpendicular pillars is circularly arrayed with an angle of 90 degrees to obtain a cosine ring unit cell structure.

9. The method for preparing a craniomaxillofacial heterogeneous metal bone implant with antibacterial properties according to claim 5, characterized in that: The double-pillar hexagonal structure array is arranged in the maxillary region; the sine ring structure array is arranged in the zygomatic region; and the cosine ring structure array is arranged in the mandibular region.

10. A craniomaxillofacial heterogeneous metal bone implant with antibacterial properties, characterized in that: The antibacterial craniomaxillofacial heterogeneous metal bone implant is prepared by the method for preparing the antibacterial craniomaxillofacial heterogeneous metal bone implant according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Organic-inorganic antibacterial composite coating on surface of medical implant and preparation method of organic-inorganic antibacterial composite coating

    CN113694255A

  • Method for 3D printing of hexagonal porous composite skeleton scaffold with positive and negative Poisson ratios

    CN115444625A

  • Preparation method of medical implanted heterogeneous metal composite structure

    CN116765425A

  • Ternary zinc alloy porous structure material as well as preparation method and application thereof

    CN118773470A

  • Medical titanium-zinc alloy as well as preparation method and application thereof

    CN119114962A

Cited By

  • Bionic design-based two-parameter function control gradient dot matrix material and filling structure thereof

    CN117469334A

  • A biomimetic design-based two-parameter function-controlled gradient lattice material and its filling structure

    CN117469334B

  • Multi-stage microporous titanium alloy loaded with nano copper selenide antibacterial peptide and preparation method of multi-stage microporous titanium alloy

    CN121265852A